Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang (Studi Pada Car Free Day Kota Padangsidimpuan) - Ayu Wandira; Rosnani Siregar; Sry Lestari (Jurnal Riset Multidisiplin Edukasi, 2026)
This research aims to analyze the influence of business capital, business location, entrepreneurial behavior, and technology on traders' income at the Car Free Day event in Padangsidimpuan City. Traders' income is not only influenced by the number of visitors, but also by their ability to manage capital, secure a strategic location, demonstrate good entrepreneurial behavior, and utilize technology in transactions and promotions. This study uses a quantitative method with data collected through questionnaires distributed to 67 street vendors operating at the Padangsidimpuan City Car Free Day using a stratified random sampling technique. The data analysis technique used is multiple linear regression analysis with the help of the SPSS version 24 program. The results of the study show that: Business capital, business location, entrepreneurial behavior, and technology have a positive and significant effect, both partially and simultaneously, on traders' income. The Adjusted R Square value of 0.547 indicates that these four variables are able to explain 54.7% of the variation in traders' income, while the remaining 45.3% is influenced by other factors outside of this study.